Manajemen Pendidikan dalam Perspektif Al-Qur'an dan As-Sunnah - Febi Febriana; Cecep Anwar (UIN Sunan Gunung Djati Bandung, 2022)
Al-Qur'an and As-Sunnah are guidelines for Muslims, among others, function as a huda which is loaded with various instructions for humans to become good caliphs on this earth. Likewise with the study of educational management, it has also been written in the Qur'an and As-Sunnah. The purpose of this study is to determine the management perspective of the Qur'an and As-Sunnah. This research is a type of qualitative research with a literature study approach. The results of the study indicate that educational management based on the Qur'an and Sunnah is a management that positions the Qur'an and As-Sunnah as a source of inspiration and guidelines that provide improvement and refinement of education management.